Pengaruh Pengasapan Ikan Model Rotasi Terhadap Kualitas Ikan Asap - Harmoko, Harmoko; Novasani, Raditya Jarwenda; Ahmudi, Ahmudi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The open smoking process has disadvantages such as uncontrolled temperature and smoke, uneven maturity and long smoking time. Another disadvantage of open-system smoking is that the preparation of fish on the stand requires labor and time. Firstly, when arranging the fish at the beginning of smoking and secondly, when turning the side of the fish. So that a lot of time is wasted and less efficient. The purpose of this research is to provide an alternative choice of fish smoking model, spread the smoke more evenly, speed up the preparation time of smoked fish. The design of the fish smoking tool uses a smoke cabinet with a rotation system. The fish holder is connected to a shaft to rotate the fish. Every 15 minutes of smoking is rotated by 45o. The results of testing the quality of smoked fish showed that the majority of respondents gave an assessment of the taste, aroma, texture and color of the fish much liked.